Assessing the Adoption of Recommended Standards, Novel Approaches, and Best Practices for Animal Health Surveillance by Decision Makers in Europe - Häsler, Barbara; Garza, Maria; Bisdorff, Betty; Léger, Anaïs; Tavornpanich, Saraya; Peyre, Marisa; Lindberg, Ann; van Schaik, Gerdien; Alban, Lis; Stärk, Katharina D. C. (Frontiers in Veterinary Science, 2019)
Animal health surveillance is an important tool for disease mitigation and helps to promote animal health and welfare, protect human health, support efficient animal production and enable trade. This study aimed to assess adoption of recommended standards and best practice for surveillance (including risk-based approaches) in Europe. It included scoping interviews with surveillance experts in Denmark, Netherlands, Norway and Switzerland to gather information on knowledge acquisition, decisions and implementation of surveillance and perceptions. This was followed by an online survey among animal health and food safety surveillance users in EU, EEA and Schengen countries. A total of 166 responses were collected from 27 countries. A strong preference for legislation and established standards was observed, with peer-reviewed publications, conferences, symposia and workshops to be major sources of information. The majority of respondents indicated a need for international evaluation for surveillance and implied that considerations of cost-effectiveness were essential when making a decision to adopt new surveillance standards. However, most of the respondents did not use a formal evaluation to inform the adoption of new standards or only conducted a descriptive assessment before their implementation or adaptation. Only a few respondents reported a quantitative economic evaluation despite economic efficiency being considered as a highly relevant criterion for surveillance implementation. Constraints mentioned in the adoption of new surveillance standards included insufficient time, financial and human resources, and lack of competency. Researchers aiming to achieve impact by their surveillance work are advised to consider ways of influencing binding standards and to disseminate their work pro-actively using varied channels of engagement tailored to relevant target audiences and their needs. Generally, a more formal linkage between surveillance information and disease mitigation decisions – for example, by using systematic evaluation – could help increase the economic value of surveillance efforts. Finally, a collaborative, international platform for exchange and learning on surveillance as well as co-design and dissemination of surveillance standards is recommended.